Millennials' willingness to pay for socially responsible investmentand its institutional and individual antecedents: Evidence from Italy, Poland, and Ukraine - Anna Doś; Monika Foltyn-Zarychta; Matteo Pedrini; Iryna Shkura (Journal of Banking and Financial Economics (JBFE), 2023)
The readiness to sacrifice profit while making socially responsible investments among millennials, as future investors and managers, was examined. Specifically, a multi-level perspective on willingness to pay for socially responsible investment was assumed to understand how nationality, personal values and investment knowledge affect millennials' readiness to sacrifice profit to achieve sustainability goals. Using survey data of 521 business students from Italy, Poland and Ukraine, it is showed that a considerable share of millennials prefer social and environmental performance of investment over financial return and that their nationality is the most powerful factor in explaining willingness to pay for socially responsible investment along with their sensitivity to environmental issues that takes the leading role among all personal values motivating investors to accept lower rates of return. The results can be relevant for financial institutions aiming at developing socially responsible investment products. Policy implications of the results are insights into nationality-related tensions while Europe-wide regulation of socially responsible investment could enter into force.
Keywords: F36; G11; G41; Q56; 330; Sustainable investment; Willingness to pay; Financial performance; Multi-level approach; Sustainable finance